The Prospect of Protecting Tomatoes From Rust - Obidjanov Dilshad Ahmed Khuja Ogli; Bakiyeva Maryam Bozorovna (Zien Journals, 2023)
If the rust mite is detected on 15% of the tomato leaves, chemical control should be carried out against it. As a result of research, insectocaricides with high biological yeffectiveness against the rust mite: Bi 58 plus 40% YeC (1,5-2,5 l/ha.), Abamectin plus 3,6% k.e. (0,1-0,2 l/ha), Golmektin, 1,8% k.e. (0,2 l/ha), Nurell D plus, 55% ye.c. (1 l/ha) these standards recommend its use against rust mites on tomatoes
Keywords: Tomato rust mite; pest; drug; chemical control